2018
DOI: 10.1002/admi.201701682
|View full text |Cite
|
Sign up to set email alerts
|

The Self‐Ordered Lamellar Texture of MoS2 Transfer Film Formed in Complex Lubrication

Abstract: In virtue of the porous microstructure and permeability of a novel MoS2 coating constituted of loosely stacked nanosheets, low viscous polyalphaolefin‐4 lubricating oil is infused to form a solid–liquid complex lubrication coating. Compared with single lubrication mode, complex lubrication shows noticeable reduction of friction as the friction coefficient is just one‐fourth of that for solid coating and half of that for lubricating oil; meanwhile, the load‐carrying capability is drastically improved by more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In contrast, the II region is filled with curved graphene with an interlayer distance of 0.33 nm. In fact, during the sliding process, superlubricity can be triggered by many factors such as the applied load, the environment, shear stress, and the frictional chemistry of the contact area [40,41]. It has also been shown that the composite films of MoS 2 produced an ultra-low friction phenomenon, which was attributed to the fact that the sliding direction was related to the friction-induced direction parallel to the shear plane of the lamellar structure [42].…”
Section: Friction Reduction Mechanism Analysismentioning
confidence: 99%
“…In contrast, the II region is filled with curved graphene with an interlayer distance of 0.33 nm. In fact, during the sliding process, superlubricity can be triggered by many factors such as the applied load, the environment, shear stress, and the frictional chemistry of the contact area [40,41]. It has also been shown that the composite films of MoS 2 produced an ultra-low friction phenomenon, which was attributed to the fact that the sliding direction was related to the friction-induced direction parallel to the shear plane of the lamellar structure [42].…”
Section: Friction Reduction Mechanism Analysismentioning
confidence: 99%
“…As a result, the in situ formation of Ag@MoS 2 nanoscrolls (NSCs) with MoS 2 sheets as rolls that wrap the nc-Ag NP cores is physically preferential. 59 Moreover, the rolling of nano-scrolls and onion-like nanostructures is more efficient in reducing motion resistance than sliding. [60][61][62] Once formed, the NSCs slide against randomly-arranged 2D MoS 2 sheets and nc-Ag NPs, which provide continuous incommensurate contact sites.…”
Section: Macro-scale Superlubricity Of the Vo-mos 2 Nwasmentioning
confidence: 99%
“…The reorientation and compaction of porous MoS 2 coating materials can be achieved by friction pretreatment, which effectively inhibits the formation of wear debris. As a result, the MoS 2 coating had good friction reduction and wear resistance [33][34][35][36]. Multi-phase composite coatings containing MoS 2 particles and diamond-like carbon [37], Si 3 N 4 [38] or CeO 2 [39] were prepared, their tribological properties were investigated and the wear mechanism was explored.…”
Section: Introductionmentioning
confidence: 99%